Analisis Gambaran Segmentasi Dan Positioning Warung Bakso Garuda - Nur Dian Sera Saputri; Semuel Batlajery (Musamus Journal of Business & Management, 2021)
The purpose of this study was to describe the market segmentation and business positioning at Warung Bakso Garuda on product sales. This study uses a qualitative approach using a descriptive type of research (illustration). In this study, there were 2 key informants and 5 supporting informants. The data analysis techniques used in this study are Data Reduction, Data Display, and Conclusions Drawing or drawing conclusions from the results of the study. The results of the study show that at this time Mopah Lama is still said to have a low monthly income, thus making consumers want a product with a relatively cheap price and easy to obtain. Differentiating the serving portion of the product is very different, but there needs to be a variety of flavors to make it more attractive to visitors. The results of interviews from 5 informants said that the service of the Garuda meatball stall was still lacking in speed of service, because the shop owner only had 1 (one) waiter, namely the shop owner himself, thus slowing down the service process.